Winter Wheat Variety Response to Timing and Number of Fungicide Applications During the 2020–2021 Growing Season in Kansas - G. Cruppe; N. Giordano; L. Ryan; L. O. Pradella; J. R. Soler; L. M. Simão; B. Valent; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this project was to evaluate the yield response of different winter wheat varieties to different fungicide management treatments during the 2020–2021 growing season in Kansas. Fourteen varieties were evaluated under four fungicide treatments (no fungicide, application either at jointing, heading, or at both stages) in four locations across Kansas in a split-plot design. Disease incidence was assessed approximately 20 d after each fungicide application. Septoria blotch and tan spot were the most prevalent early-season diseases at the studied fields, while stripe rust, leaf rust, and tan spot prevailed later in the season. While varieties responded differently to fungicide management and there was a range in yield response across locations, there was an overall yield increase of 4.2 bushels per acre resulting from the jointing fungicide application; 10.3 bu/a from the heading fungicide; and 9.9 bu/a from the combination of both applications. Although there were some similarities, the ranking of the highest yielding varieties was not uniform across locations. While different reactions occurred regarding the response of the varieties to fungicide management, overall susceptible varieties had a greater response to fungicide management compared to varieties with intermediate or high levels of genetic resistance. Our preliminary data suggest that the application of fungicide to winter wheat in Kansas might be advantageous, but the degree of this benefit will depend upon the environment, variety, and level of disease incidence.
Keywords: wheat; fungicide; timing; jointing; flag leaf; cultivars; variety